Prevalence of Temporomandibular Disorder in Undergraduate Dental Students: A Questionnaire Based Study - Alshami , Muhanad; Abdulbaqi, Hayder; Majeed, Amir (Jordan Medical Journal, 2022)
Background: Temporomandibular disorder (TMD) is a group of abnormalities in the temporomandibular joint area. Temporomandibular disorder is a multifactorial condition since multiple physiological and pathological conditions are cited as etiological factors. The clinical features include pain, clicking, deviation, limitation in joint movement, and may be associated with headache, neck ache, and disturbance in quality of life. The type of treatment depends on the cause and the severity of each case. Epidemiological studies and screening of the prevalence and clinical manifestations of temporomandibular disorder in the community could improve the preventive measures and the outcomes of treatment. Aim: To evaluate the distribution of Temporomandibular disorder among undergraduate dental students. Method: This study was a cross sectional study conducted from March until June 2020. Questionnaires were sent to undergraduate students via email. The responses to questions were given numerical values to estimate the severity of Temporomandibular disorder. The presence and severity of TMD was determined based on self-reported responses. Results: Two-thirds of respondents showed Temporomandibular disorder with different severities. The Temporomandibular disorder severity among respondents was as following: (28.2% no Temporomandibular disorder, 41.6% mild Temporomandibular disorder, 24.1% moderate Temporomandibular disorder, 6.2% sever Temporomandibular disorder). Age and the study grade were significantly associated with TMD severity. Conclusion: Despite the limitation of this study, a considerable number of students expressed signs and symptoms of Temporomandibular disorder although they are unaware of this condition.